2018
DOI: 10.1016/j.jcjd.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Type 2 Diabetes Screening Intervention in the Canadian Workplace

Abstract: This study provides a framework for future diabetes interventions in the workplace and demonstrates that workplace interventions may reduce employees' diabetes risk levels and are valued by employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“… 36 Shockey and colleagues 37 observed that the prevalence of diabetes is 6.4% among employed adults in the United States, which differed by occupation. A study of type 2 diabetes screening interventions in Canadian workplaces 38 showed that the prevalence of diabetes in the occupational population was 8% and that interventions with educational programs were effective in reducing the level of diabetes risk among employees. In the present occupational cohort, the prevalence of diabetes and hypertension was 7.1% and 39.3% in male workers.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Shockey and colleagues 37 observed that the prevalence of diabetes is 6.4% among employed adults in the United States, which differed by occupation. A study of type 2 diabetes screening interventions in Canadian workplaces 38 showed that the prevalence of diabetes in the occupational population was 8% and that interventions with educational programs were effective in reducing the level of diabetes risk among employees. In the present occupational cohort, the prevalence of diabetes and hypertension was 7.1% and 39.3% in male workers.…”
Section: Discussionmentioning
confidence: 99%
“…The location of screening may affect uptake. Screening can be provided without physician referral at dental clinics (Hadlaq et al 2017), malls (rasooldeen 2016), laboratories (Gronowski andbudelier 2020), pharmacies (lancaster et al 2018;Willis et al 2014Willis et al ), workplaces (bali et al 2018Neumann et al 2015;Padwal et al 2017;Tarride et al 2018;Wang et al 2019), and mosques (Davachi, Flynn, and edwards 2005). A mosque in Qatar hosted a diabetes event in which 3,150 worshippers underwent screening.…”
Section: Supply-side Interventionsmentioning
confidence: 99%
“…Altogether, these methods may have resulted in a nonrepresentative and biased sample that does not parallel the overall Canadian population. Still, the CANRISK score has displayed a high sensitivity for both young (<40 years of age; 83%) and older adult (!40 years of age; 93%) women with a history of gestational diabetes (45), has been strongly associated with daily steps taken (46) in older adults (!55 years of age) and has been successfully used in a workplace health intervention that resulted in a significant reduction in glycated hemoglobin in those with dysglycemia (47). These studies may, therefore, justify its use and generalizability to other Canadian samples and to young and older adults alike.…”
Section: Limitationsmentioning
confidence: 99%